Analisa Pengaruh Indeks Bursa Saham Dunia terhadap Indeks Harga Saham Gabungan Bursa Efek Indonesia Periode 2005-2011 - , Eko Suhardianto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Globalization processes that occur in the 21st century covering all aspects of life, including economic globalization, and globalization in the financial field. Successive financial crises in Asia, America, Middle East and Europe have a very rapid contagion effect as one effect of globalization. Meanwhile, the crisis also led some country to release the limitation of foreign investment, one of which is Indonesia. This indicates that theoretically the Indonesian capital market is affected by the capital markets in other countries. The purpose of this study is to analyze the influence of stock market indices in different regions of the world to the composite stock price index in Indonesian Stock Exchange using correlation and regression methods. Research object is the index of the five stock markets in the world that the author believes may affect the Indonesian Stock Exchange composite index, such as stock index of the Dow Jones Industrial Average - DJI, London Stock Exchange - FTSE 100, the composite index of the Tokyo Stock Exchange - Nikkei, Hang Seng Index - HSI, Strait Technologies Index Singapore - STI. Based on this research, it appears that not all the world stock market index has a considerable influence on Indonesian Composite Index. Order of greatest influence is the Hang Seng, Straits Times Index (STI), Dow Jones and FTSE London, while the Nikkei has a negative correlation.